3D Studies of Galaxies in Compact Groups. Issue Volume 10:Issue S309(2014) (9th February 2015) - de Oliveira, Claudia Mendes; Torres-Flores, Sergio; Amram, Philippe; Plana, Henri; Epinat, Benoit
Abstract: Fabry-Perot data of compact group galaxies have been used to show that the Tully-Fisher relation in any photometric band, for galaxies with v max > 100 km/s, is very similar to that for galaxies in other less dense environments. In the low-luminosity end, however, a few compact group galaxies fall above the relation apparently because they are too bright for their mass. Here we show that if the mass is properly computed from spectral energy distribution fitting or mass modelling, for the low-luminosity galaxies, their positions in the stellar-mass or baryonic Tully-Fisher relation are what is expected for a normal Tully-Fisher relation and the outlying positions observed in the B and K Tully-Fisher relation could be explained by brightening of the low-luminosity interacting galaxies due to strong star formation or AGN activity.